L’intelligenza artificiale generativa per l’innalzamento della qualità dell’istruzione e la fioritura del pensiero critico. Quale contributo? - Gaetano Domenici (Journal of Educational, Cultural and Psychological Studies)
Generative Artificial Intelligence for Increasing the Quality of Education and the Flourishing of Critical Thinking. What Kind of Contribution?